2000
DOI: 10.1093/oxfordjournals.schbul.a033504
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Diabetes in National Schizophrenia Samples

Abstract: People with schizophrenia may be at increased risk for Type II diabetes because of the side effects of antipsychotic medication, poorer overall physical health, less healthy lifestyles, and poorer health care. The present study uses data bases collected by the Schizophrenia Patient Outcomes Research Team (PORT) to assess the prevalence and demographic and clinical correlates of diabetes within large populations of persons receiving treatment for schizophrenia. In the Schizophrenia PORT, Medicaid and Medicare d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
292
5
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 517 publications
(322 citation statements)
references
References 54 publications
11
292
5
14
Order By: Relevance
“…These data indicate a significant decrease in whole body insulin sensitivity after oral intake of olanzapine, 10 mg/day for 10 days, after 80 min (po0.015), 100 min (po0.001), and 120 min (po0.0001) of glucose clamp. Effects of olanzapine and ziprasidone J Sacher et al population but is not associated with the risk of DM2 during antipsychotic treatment does not seem very likely given the evidence for a higher rather than a lower prevalence of DM2 in patients suffering from a major mental disorder in almost all data sets published to date (Mukherjee et al, 1996;Dixon et al, 2000;Okamura et al, 2000;Mokdad et al, 2001;Haupt and Newcomer, 2002;Newcomer et al, 2002;Ryan et al, 2003;Newcomer, 2004;Haupt et al, 2007). A second metabolic effect is depicted in Figure 2 and Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate a significant decrease in whole body insulin sensitivity after oral intake of olanzapine, 10 mg/day for 10 days, after 80 min (po0.015), 100 min (po0.001), and 120 min (po0.0001) of glucose clamp. Effects of olanzapine and ziprasidone J Sacher et al population but is not associated with the risk of DM2 during antipsychotic treatment does not seem very likely given the evidence for a higher rather than a lower prevalence of DM2 in patients suffering from a major mental disorder in almost all data sets published to date (Mukherjee et al, 1996;Dixon et al, 2000;Okamura et al, 2000;Mokdad et al, 2001;Haupt and Newcomer, 2002;Newcomer et al, 2002;Ryan et al, 2003;Newcomer, 2004;Haupt et al, 2007). A second metabolic effect is depicted in Figure 2 and Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Studying these effects in healthy volunteers minimizes the effects of lifestyle that may account for some of the impairments in glucose metabolism seen in schizophrenia patients (Mukherjee et al, 1996;Dixon et al, 2000;Ryan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the Schizophrenia Patient outcomes Research Team (PORT) field study of people with schizophrenia from 1994 to 1996, the age-adjusted prevalence of self-reported diabetes was close to 15 %, almost twice as high as the U.S. population (9.3 %). 27,28 Since that time, other reports suggest even higher rates, with the prevalence of diabetes in people with SMI typically being twofold to threefold higher than age-matched samples from the general population. 10,[29][30][31][32][33][34][35] We are aware of only two large studies examining pre-diabetes among people with schizophrenia.…”
Section: Smi and Type 2 Diabetesmentioning
confidence: 99%
“…36 Another study of Medicare enrollees with schizophrenia (N = 14,182) found that African Americans with schizophrenia had significantly higher rates of diabetes than Caucasians (15.5 % vs. 11.7 %, p < 0.001), even before the wide-spread use of SGA medications. 27 Small studies found a higher prevalence of the metabolic syndrome among Hispanics with SMI taking antipsychotics, ranging from 35 % to 74 %. 86,87 However, other studies have yielded conflicting results--with no statistically significant differences between racial/ ethnic groups.…”
Section: Particularly Vulnerable Subpopulations With Smimentioning
confidence: 99%
See 1 more Smart Citation